Development of the Social Participation Restrictions Questionnaire (SPaRQ) through consultation with adults with hearing loss, researchers, and clinicians: a content evaluation study - Heffernan, Eithne; Coulson, Neil S.; Ferguson, Melanie (Taylor & Francis, 2018)
Objective - This research aimed to evaluate the content of the Social Participation Restrictions Questionnaire (SPaRQ) in terms of its relevance, clarity, comprehensiveness, acceptability to adults with hearing loss, and responsiveness.